Greening human resource management and employee commitment toward the environment: An interaction model - Pham, Nhat Tan; Tučková, Zuzana; Phan, Quyen Phu Thi (Journal of Business Economics and Management, 2019)
In response to a greater environmental awareness, organizations are concerned more and more about the “greening” human resource management (GHRM). Although the literature on GHRM has been extending, published studies have paid little attention to the research of GHRM and its contribution to employee commitment toward the environment, especially the interactions of GHRM practices, so far. Thus, to bridge this research gap, this study extends the Ability-Motivation-Opportunity and the Social exchange theories in the green context by investigating a new conceptual framework, which explores the indirect and interactive effects of GHRM practices (training, reward, and organizational culture) on employee environmental commitment. A quantitative study is conducted through a survey involving 209 respondents. Findings suggest that: (1) three GHRM practices are important tools in stimulating directly employees to commit to the environmental activities, (2) a two-way interaction of green training and green organizational culture can unlock employee commitment for the environment, especially at the high and average levels of green organizational culture, (3) the commitment is also increased significantly through a three-way interaction, the two strongest effects are recognized with the conditions of high-green organizational culture and the average- and high-green reward, whereas (4) the interacting between green training and green reward is an unimportant factor in encouraging employee environmental attachment.